Plutarch‘s „De liberis educandis“: Educating the Virtuous Citizen - Voinič, Monika (Literatūra, 2012)
Education is an important topic in Plutarch’s corpus. Three first treatises of Moralia – De liberis educandis, De audiendis poetis and De audiendo – have the education of children as their main topic. In these works, education is presumed to be a key aspect in developing the character; good education promotes good behavior and a virtuous character; on the contrary, poor or insufficient education gives correspondingly negative results. The author of the article focuses on the first treatise, De liberis educandis, which is commonly believed to be not of the Plutarch’s authorship, however, till now it is included in the Moralia corpus because of its high importance and influence it had under the name of Plutarch. Firstly, attention is drawn to the structure and the main ideas presented in the treatise. A special attention is drawn to the role of the family in raising and educating children of the youngest age. The most vital period for the formation of character is claimed to be in childhood: thus, the importance of good education in Plutarch’s, as well as in Platonic thought, is that the character of the child is molded by reason. Closely connected with the notion of training of the irrational is the distinction which Plutarch observes between nature (physis) and character (êthos). A person’s nature is what he is born with and is unchanging. A person’s character is related to his nature, but is produced and affected by the extent to which reason influences it through quality education, and by the of his life. Plutarch assumes that the character in earliest childhood or youth is in the process of formation. Nature provides the raw material, but education and childhood, and habits more generally, play a determining role in the formation of thes adult character. By adulthood, a settled character has been attained, although the adult character may still be improved through continuing the application of reason and good habits. It should be noted that, although the lack of education and its effects are often being stated, Plutarch never points out what good education consists of, perhaps because he considered it to be obvious: music and literature, athletics and perhaps philosophy. Plutarch may be influenced by the Platonic tradition: Plato in “the Republic” talks about education as working in two stages: the first stage consists of music or literature and athletics, the second stage consisting of philosophical education (Resp. 3.401d-e, 403c-d, 7.525b-c). Finally, the author of the article analyses in more detail the parallels of the treatise with the earlier Greek tradition and discusses the influence of the earlier philosophical mind on the treatise.